The Role of Defence Diplomacy in Achieving the Goals of the UAE Foreign Policy (قضايا سياسية, 2023)
The study attempt to answer a major question related to the United Arab Emirates defence diplomacy and its attitudes towards other countries during the period 2011-2021. The research focuses on the role of defence diplomacy in achieving the objectives of the UAE foreign policy and the possibility in overcoming security challenges facing the country at regional and international levels. This study assumes that defence diplomacy has succeeded in achieving the objectives of UAE foreign policy and contributed to strengthening friendship and cooperation with other countries, and established strategic relations and developed partnerships that took into account the needs and requirements of other international partners. This research paper tried to also answer the following questions: how did defence diplomacy contribute to UAE foreign relations? What are the tools of the UAE defence diplomacy? This study applied multi-method approach, including case study and descriptive analysis. The study concluded that UAE has succeeded in adopting defence diplomacy to achieve the objectives of the its foreign policy and strengthen its relations with other countries, where the military forces played a major role through cooperation with many countries to maintain security and stability of the UAE.